Kejadian Efek Samping Kinin pada Pasien Malaria di RSUD Bontang, Kalimantan Timur - NITA RISTIAWATI (JURNAL ILMU KEFARMASIAN INDONESIA, 2015)
Quinine intravenous for severe malaria and complications, is recommended until the patient is able to use the oral formulation. The purpose of this study was to monitor the side effects that arise during the administration of quinine in malaria patients in Bontang Public Hospital and evaluate the use of other drugs that may increase the incidence of quinine side effects. This study was conducted by using descriptive study design. Monitoring of side effects is based on qualitative data, through clinical observation before and after the patients received the drug. The events of side effects were evaluated from the data collectedby usingNaranjo algorithm to determine possible (score 1-4), probable (score 5-8) and certainty (definite) (score 9). From the study, it is found that 32 patients (88.89 %) experienced quinine side effects, 2 patients (5.55 %) did not experience significant side effects. 7 patients (19.44 %) were using cimetidin, 6 patients (16.67 %) had more than 2 side effects. Possible influence of cimetidine on the clearance of quinine that cause the increase of quinine levels in the blood may increase the risk of the events of quinine side effects.